Changes of anisotropy of dilatative and optical properties of DGN crystal at ferroelectric phase transition - Andriyevsky, B.V.; Romanyuk, M.O.; Dumka, Yu.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Temperature dependences of the linear dimension L(T) and the optical path difference D(T) of the ferroelectric diglycine nitrate crystals, (NH₂CH₂COOH)₂ HNO₃, have been measured for three principal directions of optical indicatrix in the range of 130-295 K including the phase transition point Tc = 206 K. Temperature dependences of the refractivity n(T) - 1, refraction R(T), and degrees of dilatative and optical anisotropies, Aa (T) and An₋₁(T) have been calculated on the basis of the experimental dependences L(T) and D(T). Minima of the temperature dependences of spontaneous electrostriction coefficients Qij(s)(T), anisotropy degrees of dilatative (Aa) and refractive (An₋₁) characteristics close to Tc temperature show the relative disordering of DGN crystal in the temperature range near Tc. The temperature dependence of refraction R(T) of the crystal testifies the increase of dipole-dipole interaction with decreasing temperature in the wide range 295-130 K.